PENGARUH GLOBALISASI TERHADAP PERKAWINAN ENDOGAMI DI DESA TENGANAN PEGRINGSINGAN KABUPATEN KARANGASEM - Anom, I Gusti Ngurah (Jurnal Advokasi, 2016)
Tenganan Pagringsingan, grow and develop with the impression of the original as the village of Bali Aga, the village that has a pattern of life and governance communities based on the regulation of Traditional Adat Village who inherited their ancestors, including the system of marriage that has a style endogamy, As stated in awig awig " and the goods that the person has put aside his village or his female relatives or helping / giving a chance, is totally forbidden, and should be fined by the village. The impact of modernization does not make significant changes on the lives of villagers Tenganan associated with marriage endogamy, there are recorded only 15 cases from the past until now.